2017
DOI: 10.1016/j.ypmed.2017.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Associations of 100% fruit juice versus whole fruit with hypertension and diabetes risk in postmenopausal women: Results from the Women's Health Initiative

Abstract: The objective of this study was to determine whether consumption of 100% fruit juice as compared to whole fruit is associated with increased risk of hypertension or diabetes. We analyzed postmenopausal women in the United States enrolled in the Women’s Health Initiative between 1993 and 1998. Whole fruit and 100% fruit juice intake were assessed by baseline food frequency questionnaire. Standardized questionnaires assessed outcomes every 6–12 months during a mean 7.8 years of follow-up. Cox regression estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…Of a total of 16,762 publications retrieved, 21 prospective studies (8 reporting 100%FJ and 13 unspecified fruit drinks) [11][12][13][14][15][16][17][32][33][34][35][36][37][38][39][40][41][42][43][44][45] (Online Resource-Supplemental-Tables 4-5) and 35 RCTs (Online Resource-Supplemental Table 6) were identified that met the inclusion criteria (Online Resource-Supplemental Fig. 1, Online Resource-Supplemental Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…Of a total of 16,762 publications retrieved, 21 prospective studies (8 reporting 100%FJ and 13 unspecified fruit drinks) [11][12][13][14][15][16][17][32][33][34][35][36][37][38][39][40][41][42][43][44][45] (Online Resource-Supplemental-Tables 4-5) and 35 RCTs (Online Resource-Supplemental Table 6) were identified that met the inclusion criteria (Online Resource-Supplemental Fig. 1, Online Resource-Supplemental Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…The curve demonstrates a maximum benefit at doses from 100 to 150 ml/day, which is equal to a small glass of 100% fruit juice. Similar non-linear protective associations at moderate doses for 100% fruit juice consumption are also seen with stroke [13], type 2 diabetes [10], metabolic syndrome [14] and hypertension [15] (there are no studies reporting an association between 100% fruit juice and total mortality). Therefore, reporting linear or extreme comparison analysis that assumes linearity between 100% fruit juice and cardiometabolic disease outcomes would be incorrect.…”
mentioning
confidence: 86%
“…Strawberries are one of the most popular berry fruits in the world. Many studies have shown that regular fruit consumption can diminish the risk of many chronic diseases, such as hypertension, different kinds of cancer, cardiovascular diseases and overweight and obesity [1][2][3][4] due to their bioactive compound content, especially phenolic compounds and compounds with antioxidant properties [5][6][7]. According to the organic practices rules and European law, in organic farming systems, the use of pesticides and synthetic fertilizers are completely forbidden [8].…”
Section: Introductionmentioning
confidence: 99%